Women’s Beauty as Erotic Spectacle in The Apothecary Diaries Novel - Gladys Raissa Daniastuti Santoso; Akhmad Zakky; Nina Farlina; Ida Rosida (Prodi Sastra Inggris, Universitas Muhammadiyah Semarang, 2025)
Natsu Hyuuga’s novel The Apothecary Diaries Volume 1, portrays the lives of harem women confined within the patriarchal structure of the imperial court, where beauty functions as the main determinant of their value and survival. The purpose of this research is to examine how women’s beauty is narrated as an object for male characters and how the narration transforms this beauty into an erotic spectacle that exploits and oppress them. This research, using qualitative textual analysis and Laura Mulvey’s Male Gaze theory, the research shows that women’s beauty in the novel is consistently constructed through male-centered desire. Female characters are described through only their appearances such as clothing, hair, skin, and body while their opinion is silenced, reducing them as visual objects. Furthermore, the narration employs aestheticizes language, symbols and metaphors that eroticizes women into spectacles of desire. However, this eroticization of women functions as a form of exploitation, as women are valued primarily for their beauty and usefulness, then discarded once they lose their functions. These mechanisms reduce women to commodities, exchanged and manipulated to maintain patriarchal authority. In conclusion, beauty in the novel operates as a fragile tool that offers temporary recognition but simultaneously exploits women, reinforcing patriarchal power and restricting their autonomy.